Pengaruh Pemberian Pupuk Cendawan Mikoriza Arbuscular (CMA) dan Pupuk Kandang Sapi Terhadap Pertumbuhan dan Hasil Tanaman Terong Ungu (Solanum melongena L.) - Laia, Adilman; Zulfida, Ida; Miyarnis, Miyarnis (UNIVERSITAS LABUHANBATU, 2025)
This study aimed to examine the effect of Arbuscular Mycorrhizal Fungi (AMF) and cow manure fertilizer on the growth and yield of purple eggplant (Solanum melongena L.), as well as their interaction in enhancing productivity. The research was conducted using a factorial Randomized Block Design (RBD) with two factors. The first factor was AMF (M) with four levels: M0 = without AMF, M1 = 10 g/plot (100 kg/ha), M2 = 15 g/plot (150 kg/ha), and M3 = 20 g/plot (200 kg/ha). The second factor was cow manure fertilizer (P) with four levels: P0 = without cow manure, P1 = 1 kg/plot (10 tons/ha), P2 = 2 kg/plot (20 tons/ha), and P3 = 3 kg/plot (30 tons/ha). The observed parameters included plant height, number of leaves, number of branches, fruit diameter, fruit length, number of fruits per plot, and fruit weight per plot. The results showed that AMF significantly affected all growth and yield parameters. Cow manure fertilizer significantly influenced most parameters, especially fruit diameter, fruit length, number of fruits, and fruit weight. The interaction between AMF and cow manure fertilizer had a significant effect on yield parameters but was not significant for all vegetative growth parameters. Overall, the combination of 15–20 g/plot AMF with 2–3 kg/plot cow manure produced optimal growth and yield of purple eggplant..